2012
DOI: 10.1089/scd.2011.0579
|View full text |Cite
|
Sign up to set email alerts
|

Neighbor of Punc E 11: Expression Pattern of the New Hepatic Stem/Progenitor Cell Marker During Murine Liver Development

Abstract: We have previously identified Neighbor of Punc E 11 (Nope) as a specific cell surface marker of stem/progenitor cells in the murine fetal liver that is also expressed in hepatocellular carcinoma. Here, we focus on the differential expression pattern of Nope during murine fetal and postnatal liver development as well as in a normal and regenerating adult liver including oval cell activation. In the fetal liver, Nope shows a constantly high expression level and is a useful surface marker for the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“… 10 , 13 Another gene of the same imprinted gene cluster, 12 DLK1 , represents a marker of hepatic stem cells. 15 DLK1 was significantly overexpressed and its promoter was hypomethylated in human tumor tissue compared with normal samples ( P =1.3e −7 ; Figure 1a and b ) and strongly correlated with IMP2 ( R 2 =0.548; P <2.2e −16 ) and AFP ( R 2 =0.535; P <2.2e −16 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 13 Another gene of the same imprinted gene cluster, 12 DLK1 , represents a marker of hepatic stem cells. 15 DLK1 was significantly overexpressed and its promoter was hypomethylated in human tumor tissue compared with normal samples ( P =1.3e −7 ; Figure 1a and b ) and strongly correlated with IMP2 ( R 2 =0.548; P <2.2e −16 ) and AFP ( R 2 =0.535; P <2.2e −16 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we observed a correlation of IMP2 expression with the oval/stem cell marker DLK1 . 15 DLK1 was previously shown to correspond with poor survival in HCC. 34 Oval cells share phenotypic markers with embryonic hepatoblasts, in which DLK1 is also highly expressed.…”
Section: Discussionmentioning
confidence: 95%
“…During the early stages of hepatogenesis, PROM1 pos progenitor cells are more abundant than shortly after birth, indicating either cellular attrition or loss of PROM1 expression . Within 2 weeks after RRV challenge, there is a clear reemergence of PROM1 pos cells.…”
Section: Discussionmentioning
confidence: 99%
“…By quantitative real-time RT-PCR and Western blot analyses, Nope expression declined rapidly and remained barely detectable in the adult liver postnatally. Using immunohistochemical costainings for Nope- and epithelial-specific markers (E-cadherin), early hepatoblasts markers (AFP) and biliary marker proteins (CK19) revealed that Nope was initially expressed on bipotent hepatoblasts and persisted thereafter on committed hepatocytic as well as cholangiocytic progenitor cells during late fetal liver development [105]. The results indicate that Nope is a promising candidate to identify and isolate LCSCs from the adult liver.…”
Section: Markers On the Cell Surface Or Membranous Proteinsmentioning
confidence: 99%